Further exploring negative anger consequences - Kellaway, Julie A., author; Deffenbacher, Jerry L., advisor (Colorado State University. Libraries, 2009)
The nature and prediction of negative anger consequences have received limited attention from researchers. This research explored the cognitive, affective, and behavioral/expressive components of anger as predictors of anger consequences. Eight hundred and three introductory psychology students completed the Trait Anger Scale (affective), Hostile Automatic Thoughts Inventory (cognitive), Anger Expression Inventory (behavioral/expressive), Anger Consequences Scale (frequency of anger consequences), and Anger Consequences Severity Scale (severity of anger consequences in a specific situation). The Anger Consequences Scale was updated with 88 additional consequences and exploratory factor analysis revealed 12 factors: Somatic Outcomes, Physical Aggression/Injury to Others, Mixture of Severe Consequences, Hurt Self Physically, Verbal Fights, Reckless Driving, Negative School/Work Consequences, Substance Abuse, Injury to Children/Animals, Property Damage, Negative Emotions, and Vocational Consequences. Seven of 12 scales replicated earlier factors, and five were new. The frequency and severity of anger consequences did not correlate highly. Cognitive, emotional, and behavioral/expressive measures generally correlated logically with anger consequences. Hierarchical regression models explored the simultaneous contributions of sex, affective, cognitive, and expressive variables and sex x variable interactions. Variance accounted for ranged from 5.2% to 53.5% for frequency of anger consequences and from 3.8% to 15.9% for severity of anger consequences. The greatest variance predicted was for the frequency of anger leading to property damage (53.5%), physically aggression and injury to others (49.1%), and verbal fights (47.5%). Sex x anger variable interactions entered only one model. Sex, trait anger, and hostile automatic thoughts entered some models. Forms of anger expression (especially physically aggressive expression toward others or objects and verbally aggressive expressive expression) more consistency entered the regression models. In general, results indicated that: (1) the frequency of anger consequences may be better explained than the severity of anger consequences in a specific event; (2) different sets of predictors tended to predict different types of consequences (i.e., there was no common or consistent set of predictors); (3) sex, cognitive, and affective variables entered fewer models than behavioral/expressive variables; and (4) there was minimal evidence that sex moderated how variables predicted negative anger consequences. Diagnostic considerations, along with the limitations of the study, were discussed.
Keywords: anger; negative consequences; clinical psychology